Role of Serum Interleukin-6 as a Predictor of Left Ventricular Hypertrophy among Hypertensive Adults - MALIK, JAHANZAIB; RASHEED, SALEH; TOHEED, FAISAL (Pakistan Journal of Medical & Health Sciences, 2026)
Background: Hypertension is one of the biggest health problems in the world and it is closely linked to structural heart complications especially left ventricular hypertrophy (LVH). It has been found that chronic inflammation has become a primary cause of hypertensive end-organ damage, with Interleukin-6 (IL-6) a central mechanistic cause of this pathway. Nonetheless, regional statistics of Punjab and Pakistan in general are few. Aim: To test the hypothesis that serum IL-6 is a predictor of LVH in hypertensive adult patients and to test the hypothesis that serum IL-6 relates to left ventricular mass index (LVMI). Methods: The study involved a cross-sectional analytical study in tertiary care hospitals in Punjab, Pakistan, between June 2024 and May 2025. Hypertensive adults aged 30-70 years (n= 70) were enrolled. Clinical analysis, blood pressure, serum IL-6 (ELISA) and echocardiographic analyses of LVMI were conducted. LVH was considered to be LVMI greater than 115 g/m 2 in men and greater than 95 g/m 2 in women. Data analysis was done with independent t-tests, Pearson correlation, and multivariate logistic regression. Results: LVH was found in 45.7 percent of the participants. The serum IL-6 levels were much higher in the people having LVH than in those with no LVH (12.14 ± 4.52 pg/mL vs. 6.02 ± 2.48 pg/mL; p = 0.001). A positive relationship was found between IL-6 and LVMI (r = 0.61, p < 0.001). Multivariate analysis also ensured that IL-6 was an independent predictor of LVH (AOR 3.74, 95% CI: 1.827.14), when adjusted readings were done by age, BMI, systolic BP and hypertension duration. Conclusion: IL-6 levels are high predictors of LVH in hypertensive adults and can be a useful biomarker in the initial diagnosis of cardiac remodeling. Combining IL-6 measurement with the regular assessment of hypertension would improve the early risk stratification and clinical decision-making.